Studi Literatur Penerapan Human Relation dalam Organisasi - Malihah Malihah; Siti Nurlaila; Indah Mawarni; April Laksana (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Human relations or relationships between people are one of the important elements in the success of an organization. This concept includes communication, social interaction, and effective leadership within the organization. This journal aims to review the importance of human relations in increasing employee productivity and welfare, based on an analysis of several scientific journals. Based on existing literature, the implementation of good human relations contributes greatly to creating a positive work environment and increasing team effectiveness.